Radiography essentials for limited practice - Long, Bruce W.; Ehrlich, Ruth Ann , 1938-; Frank, Eugene D. (Saunders/Elsevier, 2010)
Covers various content areas mandated by the American Society of Radiologic Technologists (ASRT) curriculum, including x-ray technology and techniques, anatomy, pathology and positioning, radiation safety, patient care, and other clinical skills you may be required to perform. This title helps you to prepare for the ARRT Limited Scope Exam.